Legislative landscape for traditional health practitioners in Southern African development community countries: a scoping review. Issue 1 (7th January 2020) - Abrams, Amber Louise; Falkenberg, Torkel; Rautenbach, Christa; Moshabela, Mosa; Shezi, Busisiwe; van Ellewee, Suné; Street, Renee
Abstract : Background and objectives: Globally, contemporary legislation surrounding traditional health practitioners (THPs) is limited. This is also true for the member states of the Southern African Development Community (SADC). The main aim of this study is to map and review THP-related legislation among SADC countries. In order to limit the scope of the review, the emphasis is on defining THPs in terms of legal documents. Methods: This scoping review follows the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews methods. Two independent reviewers reviewed applicable legal definitions of THPs by searching the Southern African Legal Information Institute (SAFLII) database in April 2018 for legislation and bills. To identify additional legislation applicable in countries not listed on SAFLII and/or further relevant SADC legislation, the search engines, Google and PubMed, were used in August 2018 and results were reviewed by two independent reviewers. Full texts of available policy and legal documents were screened to identify policies and legislation relating to the regulation of THPs. Legislation was deemed relevant if it was a draft of or promulgated legislation relating to THPs. Results: Four of 14 Southern African countries have legislation relating to THPs. Three countries, namely South Africa, Namibia and Zimbabwe, have acknowledged the roles and importance of THPs in healthcare delivery by creating a council to register and formalise practices, although they have not operationalised nor registered and defined THPs. In contrast, Tanzania has established a definition couched in terms that acknowledge the context-specific and situational knowledge of THPs, while also outlining methods and the importance of local recognition. Tanzanian legislation; thus, provides a definition of THP that specifically operationalises THPs, whereas legislation in South Africa, Namibia and Zimbabwe allocates the power to a council to decide or recognise who a THP is; this council can prescribe procedures to be followed for the registration of a THP. Conclusions: This review highlights the differences and similarities between the various policies and legislation pertaining to THPs in SADC countries. Legislation regarding THPs is available in four of the 14 SADC countries. While South Africa, Tanzania, Namibia and Zimbabwe have legislation that provides guidance as to THP recognition, registration and practices, THPs continue to be loosely defined in most of these countries. Not having an exact definition for THPs may hamper the promotion and inclusion of THPs in national health systems, but it may also be something that is unavoidable given the tensions between lived practices and rigid legalistic frameworks.